Penerapan Akad Kafalah pada Jasa Garansi Bank BTN Syariah Parepare - Suwandi Kusnaedi; Muhammad Kamal Zubair; Zainal Said (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2020)
Kafalah is a guarantee given by a bank to certain parties, be it an individual, company, body or other institution in the form of a guarantee letter. The purpose of providing the guarantee is that the bank guarantees that it will pay or accept the obligations of the party that is guaranteed to the party who received the guarantee, if in the future the guarantor does not fulfill the obligations of the other party in accordance with the agreement. In the services of Bank BTN Syariah using two contracts, namely kafalah and wadi'ah. In the kafalah (guarantee) contract, the bank becomes a kafil for the customer who becomes full to bear the obligations to a party. This study uses a qualitative method. The data in this study were obtained from primary data and secondary data. With data collection techniques, namely observation, interviews, and study documentation The results of this study indicate that several things have occurred: in the guarantee mechanism there are 3 (three) parties involved, namely, the bank as the guarantor, the guarantor (the customer requesting the guarantee), and the guarantee recipient. The implementation of guarantee services at Bank BTN Syariah Parepare is carried out in several stages, namely: the application stage, the analysis stage, the processing stage, and the issuance of the guarantee, as well as the guarantee completion stage. The implementation of guarantee services at Bank BTN Syariah Parepare runs and is carried out properly by referring to the National Sharia Council (DSN) Fatwa Number: 11 / DSN-MUI / IV / 2000 concerning Kafalah. Bank BTN Syariah Parepare provides a fast service system (one day service) in issuing guarantees. With the issuance of a guarantee, it is very beneficial for both Bank BTN Syariah Parepare and for customers (principals) as users of guarantee service products. The impact for Bank BTN Syariah Parepare is that the bank receives income from the issuance of guarantees, thereby increasing the company's fee-based income. Whereas the customer (principal) can obtain a guarantee facility without requiring a large amount of collateral or cash collateral allocation, only being obliged to pay the following costs: premium costs, insurance costs, administrative costs and stamp duty fees